PENDIDIKAN KARAKTER PERSPEKTIF HAMKA - Ahmad Azizi; Hunainah Hunainah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
The purpose of this study is to identify the values ​​of character education contained in the Al-Quran surah Al-Mu'minun verses 1-9, by examining the Al-Azhar interpretation. This research is qualitative, while the method used is library research, with primary data sources from Al-Azhar interpretation, and secondary data sources for books that discuss the subject matter indirectly. Data collection techniques, validity and data analysis were used, namely documentation, theory triangulation and content analysis. The results of the author's analysis of Q.S. Al-Mu'minun verses 1-9, by examining Al-Azhar's Tafsir, that Allah SWT has determined a very large fortune for believers who have 7 (seven) good qualities, namely: being faithful, devoted to praying , turning away from things that are not useful, cleaning oneself by paying zakat, maintaining genitals, maintaining mandates and promises, and maintaining prayer. The results of the study can be concluded that there are 7 (seven) values ​​of character education that need to be taught to students from an early age, namely (1) having faith, containing honest characters found in verse 1; (2) khusyu 'in praying, contains a character of confidence, found in verse 2; (3) turning away from things that are useless, containing the character of being critical can be found in verse 3; (4) clean oneself by paying zakat, containing the caring character found in verse 4; (5) taking care of the genitals, containing the strict character found in verses 5-7; (6) maintaining the mandate and promises, containing the character of being responsible in verse 8; (7) maintaining prayer, containing the character of discipline found in verse 9.